2018
DOI: 10.1016/j.fertnstert.2018.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation genetic testing for aneuploidy is cost-effective, shortens treatment time, and reduces the risk of failed embryo transfer and clinical miscarriage

Abstract: Objective: To determine if preimplantation genetic testing for aneuploidy (PGT-A) is cost-effective for patients undergoing in vitro fertilization (IVF). Design: Decision analytic model comparing costs and clinical outcomes of two strategies: IVF with and without PGT-A. Setting: Genetics laboratory. Patients: Women % 42 years of age undergoing IVF. Intervention(s): Decision analytic model applied to the above patient population utilizing a combination of actual clinical data and assumptions from the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
95
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 22 publications
0
95
0
1
Order By: Relevance
“…This number was selected based on cumulative pregnancy rates after transfer of good embryos . Some of the embryos underwent preimplantation genetic screening, which could decrease the time to pregnancy and decrease the rate of clinical miscarriage …”
Section: Factors To Consider Before Embryo Transfermentioning
confidence: 99%
“…This number was selected based on cumulative pregnancy rates after transfer of good embryos . Some of the embryos underwent preimplantation genetic screening, which could decrease the time to pregnancy and decrease the rate of clinical miscarriage …”
Section: Factors To Consider Before Embryo Transfermentioning
confidence: 99%
“…Comparing the cost-effective outcomes on patient's age, excluded patients who have only one blastocyst, the patients > 37 years of age saved more treatment cost than patients < 35 years of age. Furthermore, this study showed that the cumulative live births of PGT-A and control groups were identical but PGT-A reduced the time in treatments up to four months, and decreased the risk of embryo transfer failure and pregnancy loss 37 . The limitation of our study is that it was a retrospective cohort study, in which we did not actively select samples for the study.…”
Section: Discussionmentioning
confidence: 71%
“…However, the sample size of PGT-A group was small, thus, the number of euploidy transferred in PGT-A group was higher (41% double embryo transfer) leading to high multiple pregnancy rate and miscarriage rate 3 . Besides, Shelby A. Neal (2018) compared the costeffective and clinical outcomes of patients with or without PGT-A 37 . Comparing the cost-effective outcomes on patient's age, excluded patients who have only one blastocyst, the patients > 37 years of age saved more treatment cost than patients < 35 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients add PGT to their IVF cycles to ensure only euploid embryos are transferred, and thereby increase their chances of delivering a healthy baby and reduce the number of cycles needed. 27 In the 2 systematic reviews, 18,19 an analysis on acupuncture's impact on relevant psychosocial outcomes was absent, yet, IVF patients are significantly burdened by infertilityrelated stress, 28,29 and insured IVF patients have cited stress as the primary reason they discontinued treatment despite not conceiving. 4 Because acupuncture is widely known to modulate stress, it could be an important way to support patients during their treatment.…”
Section: Discussionmentioning
confidence: 99%